Obesity Exacerbates Lupus Activity in Fc Gamma Receptor IIb Deficient Lupus Mice Partly through Saturated Fatty Acid-Induced Gut Barrier Defect and Systemic Inflammation - Kanyarat Udompornpitak; Awirut Charoensappakit; Kritsanawan Sae-Khow; Thansita Bhunyakarnjanarat; Cong Phi Dang; Wilasinee Saisorn; Peerapat Visitchanakun; Pornpimol Phuengmaung; Tanapat Palaga; Patcharee Ritprajak; Somkanya Tungsanga; Asada Leelahavanichkul (Karger Publishers, 2022)
The prevalence of obesity is increasing, and the coexistence of obesity and systemic lupus erythematosus (lupus) is possible. A high-fat diet (HFD) was orally administered for 6 months in female 8-week-old Fc gamma receptor IIb deficient (FcgRIIb−/−) lupus or age and gender-matched wild-type (WT) mice. Lupus nephritis (anti-dsDNA, proteinuria, and increased creatinine), gut barrier defect (fluorescein isothiocyanate dextran), serum lipopolysaccharide (LPS), serum interleukin (IL)-6, liver injury (alanine transaminase), organ fibrosis (liver and kidney pathology), spleen apoptosis (activated caspase 3), and aorta thickness (but not weight gain and lipid profiles) were more prominent in HFD-administered FcgRIIb−/− mice than the obese WT, without injury in regular diet-administered mice (both FcgRIIb−/− and WT). In parallel, combined palmitic acid (PA; a saturated fatty acid) with LPS (PA + LPS) induced higher tumor necrotic factor-α, IL-6, and IL-10 in the supernatant, inflammatory genes (inducible nitric oxide synthase and IL-1β), reactive oxygen species (dihydroethidium), and glycolysis with reduced mitochondrial activity (extracellular flux analysis) when compared with the activation by each molecule alone in both FcgRIIb−/− and WT macrophages. However, the alterations of these parameters were more prominent in PA + LPS-administered FcgRIIb−/− than in the WT cells. In conclusion, obesity accelerated inflammation in FcgRIIb−/− mice, partly due to the more potent responses from the loss of inhibitory FcgRIIb against PA + LPS with obesity-induced gut barrier defect.